PERLINDUNGAN HUKUM PENANGGUNG PERORANGAN DALAM PERJANJIAN KREDIT DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG WATES - Hastaning Pertiwi, Ratna Nindya; Nugraheni, Anjar Sri Ciptorukmi (Jurnal Privat Law, 2018)
AbstractThis article aims to determine the legal protection of individual insurers in credit agreements in PT. Bank Rakyat Indonesia (Persero) Tbk. Wates. This type of article is a descriptive empirical legal research with a qualitative approach. The data used are primary data and secondary data. Data collection techniques used interviews and literature studies. Based on the analysis, it can be seen that PT. Bank Rakyat Indonesia (Persero) Tbk. Wates has provided protection for individual insurers in credit agreements. The form of protection is the insurer may request compensation to the debtor for what he has paid, the insurer is positioned as the companion of the debtor, and the implementation of credit restructuring by the bank. Legal protection against the insurer of PT. Bank Rakyat Indonesia (Persero) Tbk. Wates has been in accordance with several provisions of the Civil Code, Act Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998, Law Number 2 Year 2014 on Amendment to Law Number 30 of 2004 Regarding Position of Notary, Bank Indonesia Regulation Number 14/15/PBI/2012 concerning Asset Quality Assessment of Commercial Banks, Regulation of the Financial Services Authority Number 42/POJK.03/2017 Concerning Obligation of Preparation and Implementation of Credit Policy Or Financing of Bank for Commercial Banks , and Circular Letter of Bank Indonesia Number 7/3/DPNP dated January 31, 2005 on Asset Quality Rating for Commercial Banks. Keywords: legal protection; credit agreemen; insurance coverageAbstrakArtikel ini bertujuan untuk mengetahui perlindungan hukum penanggung perorangan dalam perjanjian kredit di PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Wates. Jenis artikel ini adalah penelitian hukum empiris yang bersifat deskriptif dengan pendekatan kualitatif. Data yang digunakan adalah data primer dan data sekunder. Teknik pengumpulan data menggunakan wawancara dan studi kepustakaan. Berdasarkan hasil analisis, dapat diketahui bahwa PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Wates telah memberikan perlindungan untuk penanggung perorangan dalam perjanjian kredit. Bentuk perlindungan tersebut dintaranya yaitu penanggung dapat meminta ganti kerugian kepada debitur atas apa yang telah dibayarkannya, penanggung berkedudukan sebagai pendamping debitur, dan adanya penerapan restrukturisasi kredit oleh bank. Perlindungan hukum terhadap penanggung PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Wates telah sesuai dengan beberapa ketentuan pada Kitab Undang-Undang Hukum Perdata, Undang-Undang Nomor 7 Tahun 1992 Tentang Perbankan sebagaimana telah diubah dengan Undang-Undang Nomor 10 Tahun 1998, Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris, Peraturan Bank Indonesia Nomor 14/15/PBI/2012 tentang Penilaian Kualitas Aset Bank Umum, Peraturan Otoritas Jasa Keuangan Nomor 42/POJK.03/2017 Tentang Kewajiban Penyusunan Dan Pelaksanaan Kebijakan Perkreditan Atau Pembiayaan Bank Bagi Bank Umum, dan Surat Edaran Bank Indonesia Nomor 7/3/DPNP tanggal 31 Januari 2005 tentang Penilaian Kualitas Aktiva Bank Umum.Kata kunci : perlindungan hukum; perjanjian kredit; jaminan penanggungan